Effect of environment friendly weed control methods and yields of garlic (Allium Sativum L.) (Bangladesh Journal of Botany, 2025)
The research work was conducted to explore the effects of different practices of weed management upon the growth of weed and yields of garlic at the Agricultural Research Institute, Mingawara Swat, Khyber Pakhtunkhwa, Pakistan. The experiment was carried out in a Randomized Complete Block Design (RCBD) having three replications and seven weed management treatments such as T1, T2, T3, T4, T5, T6, and T7. Lowest weed density, fresh and dry biomass of weeds and maximum yield components of garlic, including average bulb weight, number of cloves per bulb, and overall bulb yield were found in treatment T5 and T6. Therefore hand weeding and the use of Eucalyptus camaldulensis leaf extract at 125 g lit-1 proved to be environmentally friendly, effective in suppressing weeds and improving garlic bulb yields.Bangladesh J. Bot. 54(4): 1089-1092, 2025 (December)